Web-based reference manager application of Dublin core in content analysis - Hernandez, Allan; Senal, Dennis David S.; Quiros, Edgardo B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2004)
One of the most pressing demands of organizations is the management of its assets in context of information exchange and allocation. The need for effective management, retrieval and distribution of relevant information both internally and externally has never been greater. Information in the form of document files, media, reports, user profiles, surveys, figures and a myriad of other sources flows in and out of the organization on a regular basis.
A Web-based Reference manager is a system that will be responsive to these information needs. It provides tools that can enable users to create and manage information assets that can easily reused by anyone in the organization. This will result in greater productivity and less downtime. Effective content analysis is the key component that will tie the different modules of reference manager together. Formulating an efficient and logical organization of information will enhance document representation and information retrieval. It will also boost precision and recall thereby promising a high degree of document relevance during searching.
In response to this need, the prototype program uses Dublin Core in analyzing, describing an representing content before being stored in the database repository. Using Dublin Core, it is hoped that a set of metadata will be formulated to be assigned as fields in a separate database to effectively represent each document.
The procedure involved 4 major phases. These phases include Field Formulation that will specify which of the Dublin Core Metadata element sets will be used as fields for the bibliographic description database. The second phase is database planning and design that includes Database management systems (DBMS) considerations, normalization and relationship definition between the tables. The third and fourth phase involved conceptual design, development and implementation of the reference manager respectively.
The web-based reference manager was created after undergoing all of these phases. The 15 Dublin core Metadata elements were trimmed to 10 relevant elements. Dataflow and Entity-relationship diagrams were used in building the database. And the PHP open source scripting language was used as the platform to develop the application.
The system created is a tool that can serve as a repository of research resources to facilitate and support the collection and sharing of information among researchers. It is equipped with data-entry and searching capabilities. And using Dublin Core elements to describe and represent each document, searching the database will result in a high degree of precision and recall.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Dublin core; Database management; Information retrieval; Web search engines